Deciphering the clinical relevance of allo-human leukocyte antigen cross-reactivity in mediating alloimmunity following transplantation. Issue 1 (February 2016) - Rowntree, Louise C.; Nguyen, Thi H.O.; Gras, Stephanie; Kotsimbos, Tom C.; Mifsud, Nicole A.
Abstract : Purpose of review: Despite a growing awareness regarding the potential of cross-reactive virus-specific memory T cells to mediate alloimmunity, there has been limited clinical evaluation on allograft immunopathology. This review will explore published models of human T-cell cross-reactivity and discuss criteria required to drive this mechanism as a contributing cause of allograft dysfunction in transplantation. Recent findings: Published models of human allogeneic (allo)-human leukocyte antigen (HLA) cross-reactivity have enabled dissection of the cross-reactive T cell receptor/peptide/major histocompatibility complex (TCR/peptide/MHC) interaction. In many of the models, the cross-reactive T cells express a unique TCR, although the relevance of a public cross-reactive TCR repertoire has yet to be determined. Equally, allopeptide identity, a vital component driving cross-recognition, remains unknown in the majority of models thereby prompting further characterization utilizing novel technologies. Although clinical studies examining the presence and impact of specific cross-reactive virus-specific T cells have been minimally explored, the existing data suggest that there may be a marginal set of requirements that need to be satisfied before the potentially damaging effects of allo-HLA cross-reactivity can be realized. Summary: Our understanding of allo-HLA cross-reactivity continues to evolve as improved technology and novel strategies allow us to better question the contribution of allo-HLA cross-reactivity in clinically relevant allograft dysfunction.